Genome-Wide Association for Itraconazole Sensitivity in Non-resistant Clinical Isolates of Aspergillus fumigatus - Zhao, Shu; Ge, Wenbo; Watanabe, Akira; Fortwendel, Jarrod R.; Gibbons, John G. (Frontiers in Fungal Biology, 2021)
Aspergillus fumigatus is a potentially lethal opportunistic pathogen that infects over ~200,000 people and causes ~100,000 deaths per year globally. Treating A. fumigatus infections is particularly challenging because of the recent emergence of azole-resistance. The majority of studies focusing on the molecular mechanisms underlying azole resistance have examined azole-resistant isolates. However, isolates that are susceptible to azoles also display variation in their sensitivity, presenting a unique opportunity to identify genes contributing to azole sensitivity. Here, we used genome-wide association (GWA) analysis to identify loci involved in azole sensitivity by analyzing the association between 68,853 SNPs and itraconazole (ITCZ) minimum inhibitory concentration (MIC) in 76 clinical isolates of A. fumigatus from Japan. Population structure analysis suggests the presence of four distinct populations, with ITCZ MICs distributed relatively evenly across populations. We independently conducted GWA when treating ITCZ MIC as a quantitative trait and a binary trait and identified two SNPs with strong associations that were identified in both analyses. These SNPs fell within the coding regions of Afu2g02220 and Afu2g02140. We functionally validated Afu2g02220 by knocking it out using a CRISPR/Cas-9 approach, because orthologs of this gene are involved in sterol modification and ITCZ targets the ergosterol pathway. Knockout strains displayed no difference in growth compared to the parent strain in minimal media, yet a minor but consistent inhibition of growth in the presence of 0.15 ug/ml ITCZ. Our results suggest that GWA paired with efficient gene deletion is a powerful and unbiased strategy for identifying the genetic basis of complex traits in A. fumigatus.